22.4k views
3 votes
1. 3x+y=5
2x-y=10

2. 2x+2y=3
X-4y=-1

User Had
by
5.7k points

2 Answers

3 votes
1. Since y in first equation is positive and y in second equation is negative, the easiest was to solve this system is:
3x+y+2x-y=5+10
5x=15
x=3

Now use the x to find y:
3*3+y=5
9+y=5
y=5-9
y=-4

2. You can either multiply the first equation by 2 so that we get the same numbers in front of the y but with different signs or simply express one of the variables and write it in second one.
First way:
2x+2y=3 /*2(multyplying by 2)

4x+4y=6 (that's our first equation)
x-4y=-1 (that's our second equation)

now we just add the equations:
4x+4y+x-4y=6+(-1)
5x=6-1
5x=5
x=1

now we find y:
1-4y=-1
-4y=-1-1
y=-2/-4
y=1/2

Second way:
We express x from the second equation and get:
x=-1+4y
now we change x in the first equation with our new x:
2*(-1+4y)+2y=3
-2+8y+2y=3
10y=5
y=1/2

x=-1+4*(1/2)
x=-1+2
x=1



User Derek Gogol
by
5.5k points
3 votes
1. X=5 and Y=-15

2. X=1 and Y=0.5
User Michael Washington
by
4.8k points